Patronage as a Means of Employment for Daughters in Educational Institutions of Ukraine at the Turn of the 19th — 20th Century - Oksana Drach (Київські історичні студії)
Patronage has existed in all societies from antiquity to the present day. The implicit meanings of expressions such as “one’s own people” and “good connections” are readily understood and utilized by the population as needed. This article aims to examine the role of patronage in the employment of women in the educational sphere of Ukraine at the turn of the 19th — 20th century. The study is based on the administrative correspondence of the Office of the Trustee of the Kyiv Educational District, specifically recommendation letters from male patrons. It has been established that patronage extended even to daughters who, upon graduating from gymnasium, obtained pedagogical qualifications. The stable employment of adult daughters was crucial to family well-being, prompting older family members to mobilize their social connections. Intense competition in the labor market among female gymnasium graduates led many to seek patrons who could facilitate their appointment to permanent positions in educational institutions. The study identifies patrons as both local high-ranking officials — such as the head of the Kyiv Provincial Gendarmerie Administration and the director of the Kyiv branch of the State Bank — and metropolitan bureaucrats, including senators. The effectiveness of patronage depended on the influence that one patron, as the author of a recommendation letter, held in the perception of another — the Trustee of the Kyiv Educational District. A distinct category of “invisible” patrons is also identified — heads of educational institutions who were consulted in advance regarding prospective candidates. The search for patrons correlated with factors such as the father’s service in government institutions and neighborly relations with local property owners. The patronage mechanism, designed to maximize the likelihood of success, operated on two levels. The first was the district administration level, requiring the approval of the district trustee and the head of his office. The second was the local administration level, which involved securing an agreement with the head of the educational institution regarding the candidate’s appointment.